Inactivation of Salmonella enterica in black peppercorn by fluidization with hydrogen peroxide vapor - Summers, Edel; Wason, Surabhi; Subbiah, Jeyamkondan; Villa-Rojas, Rossana (Frontiers in Food Science and Technology, 2023)
Salmonella is the most common bacterial pathogen associated with product recalls and outbreaks in spices. Spices are in the top three food categories for greatest number of recalls due to microbiological contamination. Current validated microbial reduction techniques for spices are tied to human health and environment concerns or negatively affect the quality characteristics of the spice which has led to the emerging of alternative technologies such as hydrogen peroxide vapor (HPV). hydrogen peroxide vapor treatment was conducted at two different temperatures (45°C and 60°C) and two dwell times (30 and 60 min). Microbial reduction and residual hydrogen peroxide were measured at three storage times: 0 h (immediately after treatment), 24 and 48 h post-treatment. The effect of HPV on the quality of whole black peppercorn was evaluated 48 h post-treatment based on changes in piperine content, total phenolics, antioxidant activity, total volatile compounds, and color. Reduction in Salmonella population ranged from 1.41–2.83 log CFU/g. Residual hydrogen peroxide of up to 500 ppm was still detected on samples after 48 h of storage. All quality parameters except for color remained unaffected between treated and untreated whole black peppercorn. The study highlights the need to explore further process design modifications before conclusions can be made on the efficacy of HPV treatment as a means for low-moisture foods pasteurization.